Students’ Speaking Anxiety In English Among First Graders of Junior High School - Mister Gidion Maru; Christy Saerang; Claudia Nivita Ante; Elizabeth Zuska Oroh; Ceisy N Wuntu; Noldy Pelenkahu (Syntax Corporation, 2022)
The purpose of this study is to investigate students’ anxiety in speaking English particularly first grader of junior high school. A quantitative inquiry, the population of study is the seventy-four first grade students of Junior High School 3 Tondano, Minahasa. The sample is one class from 3 classes are twenty-one. By relying upon the analysis on the questionnaire adopted from a final version of the PSCAS (Public Speaking Class Anxiety Scale) by Yaikhong and Usaha, the results found that three anxiety problems were most feared by students themselves; lack of vocabulary in English, and lack of good study preparation resulting in unsatisfactory learning outcomes that they produce. Therefore, collaborative activities, mutually supportive, no bullying, and prioritizing common interests that must be carried out to create a free-stress learning atmosphere in the classroom.